2001
DOI: 10.1007/bf02723241
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of congenital heart disease

Abstract: A community based survey of congenital heart disease was carried out on a random sample of 11,833 children below 15 years in Delhi, India. Congenital heart disease was diagnosed on clinical history and/or clinical examination. Out of the examined sample, 50 were found suffering from congenital heart disease, giving an overall prevalence of 4.2/1000 (4.6/1000 in boys and 3.7/1000 in girls). The prevalence rate was slightly higher than other studies carried out in the country. The reason is obvious. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 4 publications
9
54
1
3
Order By: Relevance
“…7 But in one community based study the investigators reported higher prevalence rate of CHD among Delhi children of 4.2 per 1000 of children. 12 in south Africa the prevalence of CHD among school children accounted for only 1.01 per 1000 child. [10][11][12][13][14][15] In consistent with the present finding Thakir et al 7 also observed a higher prevalence of CHD among female school going children in the age group of 5-15 years in Shimla hills, India.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…7 But in one community based study the investigators reported higher prevalence rate of CHD among Delhi children of 4.2 per 1000 of children. 12 in south Africa the prevalence of CHD among school children accounted for only 1.01 per 1000 child. [10][11][12][13][14][15] In consistent with the present finding Thakir et al 7 also observed a higher prevalence of CHD among female school going children in the age group of 5-15 years in Shimla hills, India.…”
Section: Discussionmentioning
confidence: 97%
“…[7][8][9][10][11][12] Although going by figure quoted in western countries it has been generally accepted that approximately 10 per 1000 babies are born with CHD incase of full term births. 1 Other reported a relatively lower prevalence form different countires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the BWIS, 18.5% of the patients with CHD with associated ECM were found to have a genetic syndrome. 10 In recent times, Grech and Gatt, found that 65% of the individuals with CHD and associated ECM had a recognizable genetic syndrome. 15 In the present study, 34.8% of the patients with CHD and extarcardiac malformations had a clinically recognizable syndrome.…”
Section: Prevalence Of Specific Syndromes and Associated Chdmentioning
confidence: 99%
“…Recent investigations have clearly demonstrated a much higher incidence of inherited CHDs than previously thought, and it appears more likely that genetic variation can play a role in predisposition to the majority of heart defects. 10 Hence authors intended to do a clinical study of extra cardiac malformations (ECM) associated with congenital heart disease (CHD); taking into account both their occurrence in isolation or as a part of a well-defined syndrome in a place which incidentally also has a high incidence of consanguineous marriage; thus, giving this study an added advantage of increased number of genetically acquired disorders. Since a detailed evaluation may not be possible in the community setting, this study was restricted to those children admitted in the hospital; which has also made possible to determine the prevalence of CHD in a hospital setting.…”
Section: Introductionmentioning
confidence: 99%